Komik Sebagai Media Pengajaran Bahasa Inggris Desain Bagi Mahasiswa DKV Unindra - Yohana, Fenti Mariska (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2017)
The skill of languages is so important in our life, because of this skills we can express our mind and feeling in contextual with the conversation in that situation. The ability to speak we can also speaking well, where speak or conversation have to creative figure in communication so language is clear, coherent, and easy to understand because it can express the ideas and feeling. The issue of mastery of English can not be separated from the planning of the nation's education program. The English itself is practical, still a language science that must be taught to the students. Teaching is the totality of teaching and learning activities that begin with planning and end with evaluation. More explicitly it can be said that teaching as an all-encompassing activity directly to achieve specific objectives of teaching (determining the learners' entry-behavior, drawing up lesson plans, providing information, asking questions, and assessing. Comic is one type of media that can be used to express the mind, imagination and creativity in the form of drawings and written language. Comics can encourage DKV students to enjoy the ability to speak English well. This research indicator used the elements such as comic story narrative, illustration drawings, panels, word balloons, moral values of the comic created.